Curriculum of Andalusian Indexers - Analytical Study - Pulp Indexing - sofiane, rihana; bekkaye, houaria (The Algerian Historical Journal, 2026)
Cultural life varied in Andalusia during the 7th century, where the features and features of Andalusian thought emerged from the ity of intellectual production, which could not be counted by books but by volumes, From this point of view, we have focused our intervention on the importance of the books of indexes as a manifestation of the enrichment of Andalusian heritage, based on the index of Ahmed Ben Yusuf Ben Ali Al-Fihri, as a model from which we reveal the Andalusian character during the seventh century and the level of the Andalusia.